1973
DOI: 10.1099/00207713-23-3-243
|View full text |Cite
|
Sign up to set email alerts
|

Electron Microscope Study of Whole Mounts and Thin Sections of Micromonospora chalcea ATCC 12452

Abstract: The use of whole mounts in the electron microscope study of Micromonospora chalcea is a rapid and simple method for obtaining morphologic information about both the spore and sporophore. Spore anomalies were observed by this method, and their anatomical basis was confirmed by thin sections. Spore shape and surface ornamentation varied with the age of the spore and should be taken into consideration when characterizing and comparing the spores of various isolates. The spore of M. chalcea is not an endospore as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
3

Year Published

1977
1977
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 15 publications
1
8
0
3
Order By: Relevance
“…It is possible that warts are points of preferential wall attack and synthesis with less mechanical resistance. The sporulation septum has a typical three-layered structure similar to that of the vegetative cross-wall, as has been reported previously in M. chalcea (Luedemann & Casmer, 1973) and in M. fusca and M. globosa (Stevens, 1975). The structure of the sporulation septum and its process of formation is similar to that of Streptomyces type I (Hardisson & Manzanal, 1976).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…It is possible that warts are points of preferential wall attack and synthesis with less mechanical resistance. The sporulation septum has a typical three-layered structure similar to that of the vegetative cross-wall, as has been reported previously in M. chalcea (Luedemann & Casmer, 1973) and in M. fusca and M. globosa (Stevens, 1975). The structure of the sporulation septum and its process of formation is similar to that of Streptomyces type I (Hardisson & Manzanal, 1976).…”
Section: Discussionsupporting
confidence: 72%
“…fusca, Stevens (1975) did not find mesosomes directly associated with the septum until its completion. As Luedemann & Casmer (1973) pointed out, warts are formed on the spore wall before the deposition of the material of the new layers of the spore wall has begun. Perhaps the origin of the warts is linked to the swelling of the hyphal tip at the beginning of sporogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Pseudonocardia spinosa (Henssen et al, 1983) of actinomycetes forms budding aerial hyphae resulting in spore formation. Micromonospora chalcea (Luedemann and Casmer, 1973) and Kineosporia sp. (Pagani and Parenti, 1978) of actinomycetes were also described as showing budding sporulation; however, photographs of TEM in each description indicated that those spores are formed by differentiation from the cell at the end of branched mycelia, and therefore those sporulation modes may be arthrospore formation such as Saccharomonospora and Actinomadura formosensis, not a budding mode.…”
Section: Resultsmentioning
confidence: 99%
“…Electron microscopic analysis of spores reveals the presence of warts which arise from the outer portion of the spore wall (Fig. 2), as described by Luedemann and Casmer for Micromonospora chalcea spores (16).…”
mentioning
confidence: 99%